ORGANIZATIONAL SEQUENCE, TURN-TAKING, AND ROLE-SWITCHING IN A HUMAN-ROBOT COMMUNICATION - Anggy Fian Febriyanti; Irham irham (Fakultas Komunikasi, Sastra, dan Bahasa, 2022)
Research on artificial intelligence has developed rapidly since the last fifteen years. Social studies and humanities scholars including linguists has put much attention on the relation between human-robot communications from wider and multidiscipline perspectives. Nonetheless, there is only a dearth of research investigating turn, sequence, and role-switching in humanoid interaction. Focusing on Sophia, the humanoid robot, the present study aims to examine three elements of dialogic- communication related to conversation. The present study applies a descriptive qualitative approach to investigate the research subject. Data consists of forms of utterances taken from two Sophia’s video that will be categorized into a sequence of organization, turn-taking, and role-switching functions. The results of present study show that Sophia is able to perform human-like interactional features in terms of providing adequate adjacency pairs, turn-taking, and a sequence of organizations. The present study shows that Sophia is not able to interrupt a conversation because it needs a brief moment of silence before replying.